2021
DOI: 10.1007/s42773-021-00104-3
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron X-ray microtomography and multifractal analysis for the characterization of pore structure and distribution in softwood pellet biochar

Abstract: Biochar pores in the micrometer range (1–100 µm) derive from cellular structures of the plant biomass subjected to pyrolysis or can be the result of mechanical processing, such as pelleting. In this study, synchrotron X-ray microtomography was used to investigate the internal pore structure of softwood pellet biochar produced by slow pyrolysis at 550 and 700 °C. The microtomographic data sets consisted of 2025 images of 2560 × 2560 voxels with a voxel side length of 0.87 µm. The three-dimensional reconstructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Overall, an increase in porosity, TSA, total pore volume, and VELP were observed with increasing pyrolysis temperature up to about 400-450 °C for all feedstocks. Many studies have reported an increase in the surface area, porosity and pore volume of biochar with increasing pyrolysis temperature 7,23,28,[34][35][36] .…”
Section: Visualization Of the Evolving Pore Structuresmentioning
confidence: 99%
“…Overall, an increase in porosity, TSA, total pore volume, and VELP were observed with increasing pyrolysis temperature up to about 400-450 °C for all feedstocks. Many studies have reported an increase in the surface area, porosity and pore volume of biochar with increasing pyrolysis temperature 7,23,28,[34][35][36] .…”
Section: Visualization Of the Evolving Pore Structuresmentioning
confidence: 99%
“…SEM imaging of SWP700 shows a highly porous framework consisting of macro- (Figures and S2), meso-, and micropores, which could be penetrated by water transporting dissolved Hg­(II) species. Recent studies using the same biochar show that 95% of the total porosity in SWP700 corresponds to a pore width of <3 μm, with 1.4 and 7.8% consisting of micro- (<2 nm) and mesopores (2–50 nm), respectively . Hg­(II) can be immobilized at sites on the external surface and within this porous framework.…”
Section: Resultsmentioning
confidence: 99%
“…These modified BCs had larger specific surface areas, with more exposed active sites becoming denser due to the development of a three-dimensional network structure. 41 The layered structure disappeared and a denser porous structure was produced with an increase in the amount of La-BC and Fe-BC, but the disappearance of the layered structure in Fe-BC occurred slightly later than that of La-BC. The original Fe-BC had more phenolic hydroxyl groups forming an intermolecular hydrogen bond than La-BC, but the crosslinking (relative to amino groups) density was lower.…”
Section: Discussionmentioning
confidence: 95%
“…The density of the porous structure was higher for Fe-BC than La-BC, and that of straw-modified BC was the smallest. These modified BCs had larger specific surface areas, with more exposed active sites becoming denser due to the development of a three-dimensional network structure . The layered structure disappeared and a denser porous structure was produced with an increase in the amount of La-BC and Fe-BC, but the disappearance of the layered structure in Fe-BC occurred slightly later than that of La-BC.…”
Section: Discussionmentioning
confidence: 99%